Supervision of financial markets - Ilie, Mihai; Gorgan, Alina (Annals of Spiru Haret University. Economic Series, 2016)
Based on the fundamental role of the market in contemporary economic development, in this study we aim to analyse how the financial markets in Romania are regulated, monitored and, especially supervised, compared to developed or developing European countries, close or far away from the national borders. The study highlights the main trends in the existing financial supervision systems abroad after the 2000s and ends with proposals based on the authors' opinion regarding the best option for the Romanian supervisory model of financial markets.